2014
DOI: 10.1002/phar.1448
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinical Outcomes in Nonintubated Patients with Severe Alcohol Withdrawal Syndrome Treated with Continuous-Infusion Sedatives: Dexmedetomidine versus Benzodiazepines

Abstract: DEX demonstrated a BZD-sparing effect in the treatment of AWS; however, this surrogate end point should be interpreted with caution. Although this study cannot disprove the possibility of a protective effect of DEX in preventing the requirement for endotracheal intubation in patients with AWS, an increased rate of adverse drug events and increased study drug costs were observed. If DEX is used in clinical practice, it should only be used as adjunctive therapy with BZDs that have a proven benefit in AWS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
3
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(66 citation statements)
references
References 25 publications
0
60
3
3
Order By: Relevance
“…As ɑ‐2 agonists lack the GABAergic activity to prevent and treat DT or seizures, they can only be used as adjunctive therapy to reduce autonomic hyperactivity that cannot be controlled by BZD alone 3, 80, 86. Several studies demonstrated a BZD‐sparing effect with significant reduction in BZD requirement 87, 88, 89…”
Section: Therapymentioning
confidence: 99%
“…As ɑ‐2 agonists lack the GABAergic activity to prevent and treat DT or seizures, they can only be used as adjunctive therapy to reduce autonomic hyperactivity that cannot be controlled by BZD alone 3, 80, 86. Several studies demonstrated a BZD‐sparing effect with significant reduction in BZD requirement 87, 88, 89…”
Section: Therapymentioning
confidence: 99%
“…[14][15][16][17][18][19][20][21] Mueller et al 18 conducted a randomized controlled trial involving 24 patients to evaluate dexmedetomidine as adjunctive therapy to lorazepam in patients with severe AWS. Patients were randomized 2:1 to either placebo or dexmedetomidine.…”
Section: Dexmedetomidine Use In Alcohol Withdrawalmentioning
confidence: 99%
“…Aktuell liegen sechs retrospektive Übersichten, eine prospektive Observationsstudie und eine PRCT (Prospective Randomized Controlled Trial) vor [4,6,10,11,13,16,19,20]. …”
Section: Dexmedetomidin Und Alkoholentzugsdelirvorliegende Evidenzunclassified